PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING DISERTAI SPEED TEST TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI TEKNIK SMKN 8 PADANG TAHUN PELAJARAN 2013/2014 - Trisno Putra, Ari Limay; Husna, Husna; Zulfaneti, Zulfaneti (Pendidikan Matematika, 2014)
ABSTRACT The background of this research by the students lack of understanding of mathematic concept that students look at mathematics learning outcomes of students at class XI Engineering of SMKN 8 Padang and the students lack the opportunity to share knowledge with friends. This research to determine the students understanding of mathematical concepts are taught with active learning strategies type synergetic Teaching using Speed Test better than understanding of mathematical concepts students by conventional teaching student at class XI Engineering of SMKN 8 Padang academic year 2013/2014. This research is an experimental study, the design of randomized trials on the subject. The population in this study were all students of class XI Engineering SMK 8 Padang listed school year 2013/2014 which consists of four classes. To determine the experimental class and control class is done at random, so the class XI TKJ 1 elected as experiment class and class XI TKJ 2 as control class. The instrument used in this study is a test student understanding of mathematical concepts. Form of the test used is a form of essay test with reliability 0.82. Based on the results of the analysis of the data found that both classes of normally distributed and homogeneous samples. To test the hypothesis used the t test with MINITAB, obtained P-value = 0.007. Since the P-value is smaller than α = 0.05, then reject H0. It can be concluded that the students understanding of mathematical concepts with active learning strategies type synergetic Teaching Using Speed Test better than comprehension of mathematical concepts students with conventional learning.